Late blight resistant potato hybrid clones in the VIR collection of plant genetic resources - E. V. Rogozina; N. A. Chalaya; M. A. Kuznetsova; V. N. Demidova; A. N. Rogozin; T. I. Smetanina; M. P. Beketova; O. A. Fadina; E. Е. Khavkin (Труды по прикладной ботанике, генетике и селекции)
Background. Late blight (LB) causes serious damage to potato crop. The genetic diversity of potato and their wild relatives in the VIR collection served as the basis for creating interspecific hybrids.Objective of the study. Selection of hybrid potato clones with high and long-term resistance to LB and identification of genotypes that can serve as the most promising sources of new LB resistance genes or new alleles of the already known resistance genes.Materials and methods. In 2015-2017, 45 hybrid clones with genetic material from two to nine species of Solanum L. section Petota Dumort. and six potato varieties were assessed in field conditions in the Northwestern and Central regions of Russia. The index of plant damage by P. infestans (rAUDPC), relative resistance to LB (Sx) and damage to plants at the end of growth period were determined. Thirty-six genotypes were evaluated in the lab for resistance to highly aggressive P. infestans isolates from the collection of VNIIF (All-Russian Research Institute of Phytopathology). In parallel, DNA markers were used to reveal three genes that confer broad-spectrum resistance to P. infestance (Rpi).Results and conclusions. The initial period of infection, the rate of pathogen development and the degree of potato crop damage by LB differed significantly in 2015, 2016 and 2017. The relationship between rAUDPC values in different years of study was statistically significant for hybrids and potato varieties (r = 0.87-0.94). Each year, var. 'Sarpo Mira', clones 10 / 05-09 and 50/1 KBA were highly resistant to LB (Sx = 7-8 points). As to other potato genotypes, the values of the Sx index varied between the years of the study. 'Sarpo Mira' and 12 clones, namely 38 KVA, 24-1, 24-2, 16/27-09, 4-1-2012, 118-5-2011, 39-1-2005, 50/1 KBA, 12/1-09, 171-3, 134-2-2006 and 15/13-09 were highly resistant to artificial infection with P. infestans. The average degree of consistency of potato resistance assessments in the field and laboratory experiments was established: the Spearman correlation coefficient r was 0.45-0.50 (p <0.05). In the cluster analysis, 36 potato genotypes were divided into three groups, which differed significantly in their resistance to LB under various environmental conditions. High resistance to LB correlated with the presence of resistance genes that confer broad-spectrum resistance (R8 = Rpi-smira2 in 'Sarpo Mira' and Rpi-blb1, Rpi-blb2 and Rpi-vnt1 in interspecific hybrids).